State-of-the-art gene therapy for inherited retinal disorders - O.I. Orenburkina; A.E. Babushkin (РМЖ "Клиническая офтальмология")
O.I. Orenburkina1, A.E. Babushkin2 1Russian Center for Eye and Plastic Surgery of the Bashkir State Medical University, Ufa, Russian Federation 2Ufa Research Institute of Eye Diseases of the Bashkir State Medical University, Ufa, Russian Federation Inherited retinal diseases (IRDs), which are orphan diseases, are a relevant social issue due to severe visual impairment and disability in children and working-age individuals. More than 100 IRDs caused by various defects in about 270 genes are known. Molecular genetic diagnostics is essential for identifying a specific hereditary factor of the disease. One of them is the RPE65 protein that is most highly expressed in the retinal pigment epithelium. Gene replacement therapy (GRT) with single subretinal administration of voretigene neparvovec has already been developed for hereditary retinal dystrophies caused by established biallelic mutations in the RPE65 gene, i.e., Leber congenital amaurosis 2 and retinitis pigmentosa 20. Studies (including domestic ones) have demonstrated a positive effect of this drug, particularly in children. The results of GRT for other neurological disorders have been obtained mostly in experimental studies. However, there are reasons to speak about the prospects of its future implementation in clinical practice. Keywords: inherited retinal diseases, hereditary retinal dystrophies, retinitis pigmentosa, Leber congenital amaurosis, gene replacement therapy, voretigene neparvovec. For citation: Orenburkina O.I., Babushkin A.E. State-of-the-art gene therapy for inherited retinal disorders. Russian Journal of Clinical Ophthalmology. 2024;24(1):41–45 (in Russ.). DOI: 10.32364/2311-7729-2024-24-1-8.